Analisis Variasi Produk dan Citra Merek Terhadap Kepuasan Pelanggan dan dampaknya pada Loyalitas Pelanggan (Studi pada Kopi Kenangan di Kota Semarang) - Nanda Eka S; Bambang Sutedjo (Jurnal Mirai Management, 2023)
The aim of this research is to describe and analyse the effect of Produk Variation and Brand Image on Customer Loyalty mediated by Customer Satisfaction Variables. The data collection technique uses a quaestionnaire where respondents are selected using a purposive sampling technique. The results of the descriptive analysis concluded that the results of Product Variation, Brand Image, Customer Satisfaction and Customer Loyalty were quite good. Product variety has a significant effect on customer satisfaction. Brand Image is not significant with Customer satisfaction. For the influence of significant customer satisfaction on customer loyalty. Customer satisfaction can mediate the effect of product variations on customer loyalty, as well as the effect of brand image on customer loyalty is able to mediate this influence Keywords: Product variety, brand image, customer satisfaction and customer loyalty